CREATING AS DECEPTION: THE CONCEPT OF ‘CULTURE OF ERASUREʼ IN MURIEL SPARKʼS NOVEL THE FINISHING SCHOOL - Božica M. Jović (Filolog, 2021)
This paper will deal with the peculiar, Scottish view of the position of creative imagination in literature. A specific cultural background for this view will be presented, together with the reading of one of the latest novels by Muriel Spark, The Finishing School (2004). Concepts such as ‘culture of erasure,’ ‘Calvinism’ and its cultural heritage in the modern Scotland, as well as the role ‘imagination’ plays in the national spirit against the specific Scottish historical background will be investigated into. The focus of the paper will be less on Muriel Spark as an individual author, rather, the point of the paper will be how to contextualise some themes within Spark’s novel within the specificity of a national culture and history.